Predictors of defaulting from completion of child immunization in south Ethiopia, May 2008 - A case control study - Woldie Mirkuzie; Deribew Amare; Tadesse Henoke (BMC, 2009)
Abstract Background Epidemiological investigations of recent outbreaks of vaccine preventable diseases have indicated that incomplete immunization was the major reason for the outbreaks. In Ethiopia, full immunization rate is low and reasons for defaulting from immunization are not studied well. The objective of the study was to identify the predictors of defaulting from completion of child immunization among children between ages 9-23 months in Wonago district, South Ethiopia. Methods Unmatched case control study was conducted in eight Kebeles (lowest administrative unit) of Wonago district in south Ethiopia. Census was done to identify all cases and controls. A total of 266 samples (133 cases and 133 controls) were selected by simple random sampling technique. Cases were children in the age group of 9 to 23 months who did not complete the recommended immunization schedule. Pre-tested structured questionnaire were used for data collection. Data was analyzed using SPSS 15.0 statistical software. Results Four hundred eighteen (41.7%) of the children were fully vaccinated and four hundred twelve (41.2%) of the children were partially vaccinated. The BCG: measles defaulter rate was 76.2%. Knowledge of the mothers about child immunization, monthly family income, postponing child immunization and perceived health institution support were the best predictors of defaulting from completion of child immunization. Conclusion Mothers should be educated about the benefits of vaccination and the timely administration of vaccines.